Personality factors in heart transplant recipients - M. A. Simonenko; P. A. Fedotov; P. V. Shirobokova; Yu. V. Sazonova; M. A. Bortsova; A. V. Berezina; M. A. Karpenko (Вестник трансплантологии и искусственных органов, 2020)
Objective: to assess the personal psychological profile of heart transplant recipients as the first stage in the development of post-transplant personalized rehabilitation programs. Materials and methods. From January 2010 to July 2019, 129 HTs were performed (mean age 46.6 ± 14.1 years; 74% (n = 95) were men, 26% (n = 34) were women). All patients in the heart transplant waiting list were examined by a clinical psychologist and a psychotherapist to exclude contraindications to transplant surgery. To assess personal traits, we used the standard multifactorial questionnaire by Cattell R., 16 PF (version A), which included 187 questions. Heart transplantation and absence of post-transplant severe cognitive impairments were the selection criteria for this study. Patients were surveyed before they were discharged from the hospital – 30–60 days following HT: during the period of complete recovery after surgery. In the present study, a retrospective assessment of the results was performed in 107 patients (n = 76 – men; n = 31 – women). Results. Analysis of the personality portrait revealed that over half of recipients were reserved, distant (factor A – schizothymia) and restrained (factor F – restraint; F2 – introvert; F4 – conforming) with lower mental capacity (factor B), and were shy, timid (factor H), with low super ego (factor G: irresponsible, tolerates disorder, flexible, open to change). Our results showed that 47% of patients (n = 18 out of 38 patients, n = 22 are pensioners) with a weak degree of factor C (reactive, affected by feelings) are workers to 42% (n = 29 out of 69, n = 28 – retirees) with a strong degree of the same factor. One year after HT, the number of physically active patients was higher among those with low anxiety compared with high anxiety (41% (18 of 44) and 32% (20 of 63), respectively, p = 0.41). Conclusion. Personality factors are non-modifiable characteristics of patients. They affect human behavior, return to work and to social life, as well as physical and psychological recovery from HT. Knowing the personal traits of recipients would allow to develop a personalized approach to their rehabilitation and a technique for timely examination after HT.